Validity of Electronic Documents as a Tool of Evidence in Divorce Decisions at East Jakarta Religious Court - Fahmi Azis; Imam Haryanto (Journal Research of Social Science, Economics, and Management, 2022)
The rapid development and advancement of information technology has led to changes in human life which directly affect the birth of new forms of legal action. Activities through the media of electronic systems, also known as cyberspace. This study aims to determine the validity of divorce through social media (electronic) in divorce cases in the Religious Courts, to analyze the judge's legal considerations on social media evidence in divorce cases in Decision Number 1528/Pdt.G/2017/PAJT and to determine the validity of the divorce. through social media (electronic) in the perspective of Islamic law and legislation in Indonesia. This study uses normative legal research, namely by studying the literature, laws and regulations, and writings that are closely related to the problem under study. This research uses the Information Search Literature Study and the data needed in several sources. Preparation using literature study is done by reading, studying and analyzing literature or books and other sources related to the research theme. Deductive data analysis is a procedure that begins with a general event, the truth of which is known or believed, and ends at a conclusion. According to Islamic law, divorce is through online media such as telephone, Facebook, Youtube, SMS, Whatsapp, or Instagram, whether it is only in the form of sound or accompanied by the form of the party communicating in the form of an image (video call). Then according to the Shari'a, the divorce is declared as a valid divorce, even though there is no guardian and it is not delivered directly in front of the wife. According to positive law, it is in line with the provisions in Islamic law which regulates divorce, namely the arrangement in KHI comes from Islamic law. However, the absence of legality in the form of proof of divorce (with no divorce being handed down in court), namely through online media will indeed have an impact on marital status problems and other legal problems that may arise so that Muslims also need to comply with state law.